2014
DOI: 10.1002/jcp.24366
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐195 Chemosensitizes Colon Cancer Cells to the Chemotherapeutic Drug Doxorubicin by Targeting the First Binding Site of BCL2L2 mRNA

Abstract: The mechanisms underlying doxorubicin (Dox) resistance in colon cancer cells are not fully understood. MicroRNA (miRNA) play important roles in tumorigenesis and drug resistance. However, the relationship between miRNA and Dox resistance in colon cancer cells has not been previously explored. In this study, we utilized microRNA array and real-time PCR to verify that miR-127, miR-195, miR-22, miR-137 were significantly down-regulated, while miR-21, miR-592 were up-regulated in both HT29/DOX and LOVO/DOX cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 51 publications
1
45
0
1
Order By: Relevance
“…At present, the application of doxorubicin, a DNA‐intercalating anthracycline antibiotic, in combination with other anti‐tumor drugs exhibits good therapeutic effects against late‐stage CC (Qu et al, ). However, chemoresistance is a frequent event and inhibits the clinical application of chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the application of doxorubicin, a DNA‐intercalating anthracycline antibiotic, in combination with other anti‐tumor drugs exhibits good therapeutic effects against late‐stage CC (Qu et al, ). However, chemoresistance is a frequent event and inhibits the clinical application of chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Liu et al and Chen et al proved that EZH2 promoted the progression and invasion of human gastric cancer [26, 27]. BCL2L2 was determined to promote tumorigenicity and invasion in human glioblastoma, non-small-cell lung cancer, and colon cancer [2830]. CDH2 was reported to be related to the epithelial-mesenchymal transition (EMT) in non-small-cell lung cancer [31].…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al׳s study 128 found that miR-21 was involved in gemcitabine resistance by directly upregulating BCL-2 expression in pancreatic cancer cells. Other miRNAs found to directly target BCL-2 using Western blot and luciferase activity assays include miR-497 129 , miR-200bc/429 cluster 130 , miR-1915 131 , miR-214 132 miR-195 133 , and miR-205 134 .…”
Section: Aberrant Expression Of Mirnas and Cancer Drug Resistancementioning
confidence: 99%